Rural land subdivision and suburbanisation in the peri-urban area, Kairanga County (1970-1980) : a thesis presented in partial fulfilment of the requirements for the Degree of Master of Arts in Geography at Massey University - Prangkio, Chira (Massey University, 1980)
After briefly outlining the patterns and processes of rural land subdivision and suburbanisation in other parts of New Zealand, the thesis examines the rural land subdivision regulations and policies throughout the country. The development of a number of small size farmlets in the peri-urban areas has been an indicator of urban expansion in parts of the country. This study is based upon the Kairanga County, a rural area surrounding the city of Palmerston North. In the introduction the county is described as it relates to the rural land subdivision situation. The study of size of holding refers to those farmlets with an area of 20 hectares or less. It was found that most dwellings in the study area which had been built in the 1970s were concentrated upon 'subdivision' land. These farmlets or holdings also illustrated the patterns of change in land use and land holdings. There has been an increase in the number of dwellings in the rural area of the county, especially in 'subdivision' areas, with an average of more than sixteen houses per year. A small percentage of rural 'subdivision' landowners work full-time on their holdings but most of them are employed in non-farming occupations and only carry on part-time farming activities on their lands. There are 61 percent of all those employed in the county engaged in the non-farming occupations. It was found that there are more 'potential' subdivisions than 'actual' subdivisions both in terms of total area and of total numbers of holdings. Most small holdings tend to be located closer to the Palmerston North Urban Area. The total number of holdings has increased because larger holdings have been subdivided into smaller-sized holdings. The area of 'subdivision' land in holdings of 20 hectares or less represents 23 percent of the total occupied land in the county. The land use patterns of 'subdivision' land have changed with a greater variety of land uses and farming types. There was an average of at least two separate types of land use or farming on each holding. Some 5,003 hectares of land in the county has been legally subdivided for smaller farmlets each with an area of 20 hectares or less. When these farmlets become 'actual' subdivisions most of them would be in part for residential use and eventually add to the peri-urban area around Palmerston North City. Finally it was concluded that the pattern and process of suburbanisation of Kairanga County will continue as long as 'potential' subdivision land is available for settlement.
Keywords: Kairanga County New Zealand; Rural; Land use; Land subdivision; Suburban life